Asuhan Keperawatan Keluarga Dengan Hipertensi - Sarah Dwi Astuti; Lucia Firsty Puspita Krishna (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2019)
The family is a group of two or more people who live together through marriage ties, and the emotional closeness that each identifies as part of the family. Family nursing services that are currently being developed are part of public health services. One problem that often occurs in families is hypertension. Families with family members who experience hypertension at this time, are found in the environment around us, both come from family members themselves and other family members. These problems can occur due to various factors or causes. One of the causes is age, sex, race, lifestyle, heredity, personal characteristics and habits of life. To overcome problems in families with hypertension, comprehensive nursing care is needed by using a nursing process where nurses have an important role in providing nursing care, namely promotive, preventive, curative and rehabilitative aspects.